COOPERATIVE LESSON PLAN IN DEVELOPING AUTISTIC CHILDREN’S SOCIAL INTERACTION SKILL (Proceedings of International Conference on Special Education, 2015)
In some cases and literature, it is explained that one of the issue which is faced by autistic children is social interaction. As social being or individual, interaction is one of the important aspects which always be faced in daily life and it is not exception for autistic children. School is an institution that responsible to develop their students’ skills in every aspect. Besides that, school is also a miniature of social life which interaction process takes place and makes the school a facility for developing social interaction skill especially for autistic children. Autistic children’s social interaction can be developed with effective methods by the schools particularly the teachers. One of the effective methods is cooperative learning. This research used literature study in establishing a proper lesson method design for autistic children on developing their social interaction skill. Reviewing from several aspects of cooperative learning, this method can help developing autistic children’s social interaction skill. This method is useful because every student has responsibility to himself and to his classmates by communicating more intensively among themselves.